2021
DOI: 10.29303/jpmpi.v4i3.851
|View full text |Cite
|
Sign up to set email alerts
|

Sosialisasi Pendampingan Asupan Gizi Atlet Muda di Kota Palangka Raya pada Masa Pandemi Covid-19

Abstract: For an athlete to get a complete nutritional intake with the right portion of food, will make the athlete's body can function to the maximum, so that performance will also be maximal when doing competitions. Therefore, it is important for an athlete to really attention to his nutritional intake, especially the balance between nutritional intake and energy expenditure, both in the phase before, during, and after a match or exercise. Because energy will affect the performance of athletes, as well as the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…This is in line with what was said by the Ministry of Health of the Republic of Indonesia revealed that prevention efforts carried out to break the chain of spread of COVID-19 include socializing the Social Distancing Movement, requiring masks, diligently washing hands using soap or alcohol, and diligently exercising which are all part of clean and healthy living behavior. (Harvianto &;Sakti, 2021) ( Wismanadi et al, 2021) Based on the results of interviews conducted with teachers, the students of SMP Negeri 3 Katingan Tengah are still very minimal in getting education about clean and healthy living behavior. In order to provide solutions to these existing problems, it is necessary to hold an educational activity in the form of socialization about clean and healthy living behavior in the school.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with what was said by the Ministry of Health of the Republic of Indonesia revealed that prevention efforts carried out to break the chain of spread of COVID-19 include socializing the Social Distancing Movement, requiring masks, diligently washing hands using soap or alcohol, and diligently exercising which are all part of clean and healthy living behavior. (Harvianto &;Sakti, 2021) ( Wismanadi et al, 2021) Based on the results of interviews conducted with teachers, the students of SMP Negeri 3 Katingan Tengah are still very minimal in getting education about clean and healthy living behavior. In order to provide solutions to these existing problems, it is necessary to hold an educational activity in the form of socialization about clean and healthy living behavior in the school.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to psychology, other factors affect the athlete's physical condition, namely the intake of food and nutrition obtained during the COVID-19 pandemic. (Harvianto, Wire, & Sakti, 2021) revealed that it is essential for an athlete to pay attention to his nutritional intake, especially the balance between nutritional information and energy expenditure, both in the phases before, during, and after a match or sport. Because energy will affect the athlete's performance, maximum athlete performance will support him to achieve the best performance.…”
Section: Introductionmentioning
confidence: 99%